Pengaruh Budaya Organisasi terhadap Kinerja Karyawan - Putri Widya Rezki Pratama; Wahib Assyahri (Jurnal Ilmu Sosial dan Humaniora, 2024)
Organisational culture encompasses a set of values, norms and practices that are applied in the workplace and influence employee behaviour and attitudes. An organisational culture that is not inclusive can create a hostile and unsupportive work environment, which can lead to decreased motivation, dissatisfaction, and even decreased performance among employees who feel unrecognised or discriminated against. To improve employee performance, it is important to have a positive organisational culture. The existence of organisational Culture has a significant impact on change, thus becoming a key driver in the advancement of employee performance within an organisation. This research aims to reveal in more detail the influence of organisational culture on employee performance. The research method used is a literature review with a qualitative approach. This research data was collected by referring to previous research conducted in the 2019-2024 period. The results of this study indicate from the indicators of organisational culture put forward by Robbins and Judge that a stable and supportive organisational culture has a significant influence in improving employee performance. This emphasises the importance for organisations to build and maintain a positive organisational culture in order to achieve optimal employee performance. In addition, a balance between cultural stability and flexibility is necessary for organisations to adapt to changes in the external environment.